Ultrasonic Sensor-Based Automatic System for Indonesian Army Physical Fitness Training - Ahmad Lukman Nur Rokhim; Syafrian Herlukman; Jeki Saputra (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
Physical fitness is an important factor in supporting the performance and physical readiness of Indonesian Army members. Fitness exercises such as pull-ups and shuttle runs are often used to measure fitness levels. However, manual measurements that have been carried out so far have the potential to cause human error and are less efficient in terms of time and accuracy. To overcome these obstacles, this study aims to develop an automatic system based on ultrasonic sensors that can detect and calculate fitness activities in real-time. The system is designed by integrating ultrasonic sensors to detect changes in distance generated by body movements during pull-ups and shuttle runs. Data from the sensors is processed by a microcontroller to calculate the number of pull-up repetitions or shuttle run travel time. The calculation results are displayed on the LCD screen, providing ease of monitoring and recording data. The research methodology includes hardware design, microcontroller-based software development, and system testing to measure its accuracy and reliability. The test results show that this system has an accuracy of up to 96% in detecting pull-up movements and 94% in measuring shuttle run time. In addition, this system speeds up the fitness evaluation process by eliminating the need for manual calculations. With the implementation of this automated system, physical fitness training in the Indonesian Army environment can be carried out more efficiently, measurably, and accurately. This technology also has the potential to be applied to other fitness activities to support the modernization of physical evaluation in military institutions.